Evaluasi Pembelajaran Daring Dengan Menggunakan Aplikasi Zoom di Masa Pendemi Covid-19 Pada Mata Kuliah Pengantar Asuhan Kebidanan - Desy Syswianti; Naning Suryani; Tri Wahyuni (Jurnal Medika Cendikia, 2020)
Covid-19 pandemic which is currently affecting almost all countries in the world including Indonesia has an impact on the world of education. An online home study policy was adopted to protect students from Covid-19 exposure. The purpose of this study was to determine students' perceptions of online learning by using the Zoom application in the introductory of midwifery care course, and to determine the effectiveness of learners in terms of student achievement. The research is a descriptive study with a mixed method. The population is all STIKes Karsa Husada Garut students who take introductory of midwifery care courses. The quantitative sample was taken by students in grade 1A. The qualitative sample was taken by 4 students who actively participated in all lecture and communicative activities. Retrieval of data using the final semester exam documentation, and interviews. Data analysis is a qualitative approach with interactive analysis of Miles and Huberman, and a quantitative approach with one sample t test. The results showed that students' perceptions were not good towards learning in introductory of midwifery care courses with the Zoom application during the Covid-19 pandemic, because: 1) the Zoom application requires a large internet quota; 2) There is noise due to microphone quality problems and / or noise interference from the student environment that does not turn off the microphone; 3) students are less focused because learning is done from their homes, because the connection is lost due to bad signals, and there is no direct supervision from the lecturer. Learning in midwifery introductory courses with the Zoom application is not effective when viewed from learning achievements